Trajectories of Brain Lactate and Re-visited Oxygen-Glucose Index Calculations Do Not Support Elevated Non-oxidative Metabolism of Glucose Across Childhood - Benveniste, Helene; Dienel, Gerald; Jacob, Zvi; Lee, Hedok; Makaryus, Rany; Gjedde, Albert; Hyder, Fahmeed; Rothman, Douglas L. (Frontiers in Neuroscience, 2018)
Brain growth across childhood is a dynamic process associated with specific energy requirements. A disproportionately higher rate of glucose utilization (CMRglucose) compared with oxygen consumption (CMRO2) was documented in children’s brain and suggestive of non-oxidative metabolism of glucose. Several candidate metabolic pathways may explain the CMRglucose-CMRO2 mismatch, and lactate production is considered a major contender. The ~33% excess CMRglucose equals 0.18 mol glucose/g/min and predicts lactate release of 0.36 mol/g/min. To validate such scenario, we measured the brain lactate concentration ([Lac]) in 65 children to determine if indeed lactate accumulates and is high enough to 1) account for the glucose consumed in excess of oxygen and 2) support a high rate of lactate efflux from the young brain. Across childhood, brain [Lac] was lower than predicted, and below the range for adult brain. In addition, we re-calculated the CMRglucose-CMRO2 mismatch itself by using updated lumped constant values. The calculated cerebral metabolic rate of lactate indicated a net influx of 0.04 mol/g/min, or in terms of CMRglucose, of 0.02 mol glucose/g/min. Accumulation of [Lac] and calculated efflux of lactate from brain are not consistent with the increase in non-oxidative metabolism of glucose. In addition, the value for the lumped constant for [18F]fluorodeoxyglucose has a high impact on calculated CMRglucose and use of updated values alters or eliminates the CMRglucose-CMRO2 mismatch in developing brain. We conclude that the presently-accepted notion of non-oxidative metabolism of glucose during childhood must be revisited and deserves further investigations.